Vaccine nation : America's changing relationship with immunization - Conis, Elena (Chicago : University of Chicago Press, 2015)
While vaccination rates have soared and cases of preventable infections have plummeted, an increasingly vocal cross section of Americans have questioned the safety and necessity of vaccines. In Vaccine Nation, Elena Conis explores this complicated history and its consequences for personal and public health.
Kennedy's vaccination assistance act -- Polio, measles, and the "dirty disease gang" -- How serious is mumps? -- Carter's childhood immunization initiative -- A mother's responsibility -- Tampering with nature -- Clinton's vaccines for children program -- Sex, drugs, and hepatitis B -- Vaccine risks and the new media -- Sex, girls, and HPV.
Includes bibliographical references and index.
Keywords: Vaccination -- United States -- History -- 20th century; Vaccination -- history; History, 20th Century; Mass Vaccination -- legislation & jurisprudence; Child; Government Regulation; Health Knowledge, Attitudes, Practice; United States; MEDICAL -- Immunology; Vaccination; United States; Impfung; Kontroverse; USA; 1900-1999; History